Penerapan Metode Multi Factor Evaluation Process Pada Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Berbasis Key Performance Indicator - Novita Iman Sari (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
In determining the assessment of employee performance in the Zeribowl group, several assessment factors are needed. The assessment factor consists of 4 alternative factors according to the standard vision and mission in the company. The alternatives include the number of working days, attendance discipline, report accuracy, customer complaints. Employee performance measurement must be carried out with proper consideration in providing an assessment of employee performance using a collective approach to the decision-making process. The current employee performance appraisal process is still carried out subjectively and based on an assessment that has been determined by the company, so that sometimes it causes dissatisfaction and injustice and raises questions. The resulting data becomes more accurate because it is in accordance with the existing facts. The settlement method used in this study is the Multi Factor Evaluation Process (MFEP) based on Key Performance Indicators (KPI). The results of this research will produce an alternative that helps the company to provide a decision based on the results of the best employee performance appraisal.